Endocytic trafficking of silica nanoparticles in a cell line derived from the organ of Corti. (February 2013) - Pritz, Christian Oliver; Bitsche, Mario; Salvenmoser, Willi; Dudás, József; Schrott-Fischer, Anneliese; Glueckert, Rudolf
Background: Due to their biochemical versatility, nanoparticles (NPs) have become one of the most important future carriers for drugs and genes. NP-mediated delivery could enable an effective pharmacotherapy to the inner ear and combat hearing loss.Aims: This study investigates the endocytic trafficking of silica NPs within HEI-OC1 cells, a cell line derived from the inner ear.Materials & methods: To investigate the interaction between 50-, 70- and 100-nm silica NPs and the cells, the authors employed a set of commonly available methods involving light and electron microscopy, and sample processing methods, which preserve the native cell shape and the fragile endocytic structures.Results: The authors observed that 50-nm NPs were the most efficiently internalized. They also identified macropinocytosis as the dominant mechanism of uptake, showed localization of NPs in the early endosome and observed that silica NPs were delayed during trafficking to the lysosomes, where these NPs stayed confined, showing no endosomal escape.Conclusion: These silica NPs mostly rely on macropinocytosis for internalization. A successful use of silica NPs as vectors would involve smaller NPs and an endosomal escape strategy. Original submitted 21 December 2011; Revised submitted 23 May 2012; Published online 14 August 2012